Early focal brain injury after subarachnoid hemorrhage correlates with spreading depolarizations. (22nd January 2019) - Eriksen, Nina; Rostrup, Egill; Fabricius, Martin; Scheel, Michael; Major, Sebastian; Winkler, Maren K.L.; Bohner, Georg; Santos, Edgar; Sakowitz, Oliver W.; Kola, Vasilis; Reiffurth, Clemens; Hartings, Jed A.; et al.
Abstract : Objective: To investigate whether spreading depolarization (SD)-related variables at 2 different time windows (days 1–4 and 5–8) after aneurysmal subarachnoid hemorrhage (aSAH) correlate with the stereologically determined volume of early focal brain injury on the preinterventional CT scan. Methods: In this observational multicenter study of 54 patients, volumes of unaffected brain tissue, ventricles, cerebellum, aSAH, intracerebral hemorrhage, and focal parenchymal hypodensity were stereologically estimated. Patients were electrocorticographically monitored using subdural electrodes for 81.8 hours (median) (interquartile range: 70.6–90.5) during days 1–4 (n = 54) and for 75.9 (59.5–88.7) hours during days 5–8 (n = 51). Peak total SD-induced depression duration of a recording day (PTDDD) and peak numbers of (1) SDs, (2) isoelectric SDs, and (3) spreading depressions of a recording day were determined following the recommendations of the Co-Operative Studies on Brain Injury Depolarizations. Results: Thirty-three of 37 patients with early focal brain injury (intracerebral hemorrhage and/or hypodensity) in contrast to 7 of 17 without displayed SDs during days 1–4 (sensitivity: 89% [95% confidence interval, CI: 75%–97%], specificity: 59% [CI: 33%–82%], positive predictive value: 83% [CI: 67%–93%], negative predictive value: 71% [CI: 42%–92%], Fisher exact test, p < 0.001). All 4 SD-related variables during days 1–4 significantly correlated with the volume of early focal brain injury (Spearman rank order correlations). A multiple ordinal regression analysis identified the PTDDD as the most important predictor. Conclusions: Our findings suggest that early focal brain injury after aSAH is associated with early SDs and further support the notion that SDs are a biomarker of focal brain lesions.